ZAKAT GOVERNANCE IN PANGKALPINANG CITY INSTITUTIONAL ECONOMIC PERSPECTIVE - Lidyawati, Lidyawati; Rozi, Rozi; Rohmadania, Siti; Kurnia, Muhammad; Hayatullah, Imam Khomaeni (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
This research aims to find out the governance of zakat from the perspective of institutional economics in Pangkalpinang City. This research uses qualitative-descriptive method. Data collection methods through interviews, documentation and observation. The results of this study are the management of zakat in BAZNAS Pangkalpinang City every year continues to increase, although there is still a lack of public awareness in Pangkalpinang City in paying zakat. In its journey in the third year of BAZNAS leadership, the progress has been seen where public trust in BAZNAS began to emerge. BAZNAS Pangkalpinang City has made many programs covering education, humanitarian and poor people's programs to provide welfare to the community with professional and trustworthy zakat management.